Characteristic time of stellar flares on Sun-like stars. Issue 1 (12th June 2021) - Yan, Y; He, H; Li, C; Esamdin, A; Tan, B L; Zhang, L Y; Wang, H
ABSTRACT: Using the short-cadence data (1-min interval) of the Kepler space telescope, we conducted a statistical analysis for the characteristic time of stellar flares on Sun-like stars (SLS). Akin to solar flares, stellar flares show rise and decay light-curve profiles, which reflect the two distinct phases (rise phase and decay phase) of the flare process. We derived characteristic times of the two phases for stellar flares of SLS, resulting in a median rise time of about 5.9 min and a median decay time of 22.6 min. It is found that both the rise time and the decay time of the stellar flares follow a lognormal distribution. The peak positions of the lognormal distributions for flare rise time and decay time are 3.5 min and 14.8 min, respectively. These time values for stellar flares are similar to the time-scale of solar flares, which supports the idea that stellar flares and solar flares have the same physical mechanism. The statistical results obtained in this work for SLS can be a benchmark of flare characteristic times when comparing with other types of stars.